Agricultural Innovation Systems in Africa workshop - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Coorganised by Joint Learning in Innovation Systems in African Agriculture (JOLISAA), CCAFS and other partners, the Agricultural Innovation Systems in Africa (AISA) was held on 29–31 May 2013 in Nairobi, Kenya. AISA brought together researchers and development practitioners who held discussions through oral plenary sessions, group work, open space sessions and a poster and market place session on Agricultural Innovation systems. Photos: V. Atakos (CCAFS).